Granulocytic Sarcoma of Parotid Gland in a 4-Year-Old Child with Subleukemic AML: A Diagnostic Challenge!. (4th September 2013) - Ingale, Yashwant; Patil, Tushar; Chaudhari, Priyanka; Routray, Samapika; Agrawal, Manoj
Abstract : A 4-year-old male child presented to our outpatient department with large swelling in the parotid region. Routine investigations were all within normal limits, and evaluation of complete blood count was normal except for anaemia. Excisional biopsy as a therapeutic diagnosis was done. Microscopic examination showed monomorphic population of discohesive, hyperchromatic small round cells having high N : C ratio, coarse chromatin, conspicuous nucleoli, and sometimes angulated nuclei lying in sheets. Immunohistochemistry was done to rule out possible differential diagnosis. Fine needle aspiration from the swelling showed predominant population of blast cells. Myeloperoxidase and PBO were strongly positive, and diagnosis of granulocytic sarcoma was confirmed.